Formamidinesulfinic Acid‐Functionalized Fe3O4@SiO2 as a Green and Magnetic Recyclable Catalyst for Synthesis of Pyrano[2, 3‐d] pyrimidinone Derivatives. Issue 6 (12th February 2018) - Ghandi, Leila; Miraki, Maryam Kazemi; Radfar, Iman; Yazdani, Elahe; Heydari, Akbar
Abstract: Formamidine sulfonic acid (FSA) stabilized on silica‐coated Fe3 O4 magnetic nanoparticles as an efficient and hydrogen bonding catalyst was employed for Knoevenagel condensation and synthesis of pyrano[2, 3‐d]pyrimidinone derivatives by the one‐pot three‐component condensation reaction in water at room temperature. The catalyst can be separated from the mixture reaction which is in close agreement with green chemistry disciplines. Abstract : Formamidine sulfonic acid (FSA) stabilized on silica‐coated Fe3 O4 magnetic nanoparticles as an efficient and hydrogen bonding catalyst was employed for Knoevenagel condensation and synthesis of pyrano[2, 3‐d]pyrimidinone derivatives by the one‐pot three‐component condensation reaction in water at room temperature.